2018
DOI: 10.30630/polingua.v5i1.28
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Need Analysis on English Learning Material at Mechanical Metal in SMK N 8 Padang

Abstract: Mechanical students need material in English subject that relevant with their department. However, most of the teachersused the materials that are general English to teach English in the mechanical department. Thus, in this research the writer did it toknow the students’ need. In this research, the samples are the students in the mechanical metal department. There are two classeswhich are 45 students. The writer took 15 students through technique sampling is sample random sampling. The instrument thatwriter us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The students can be invited to provide any pieces of information about what they need to learn in English through a study. In fact, need analysis has been seen as an important part of ELT at SMK since researchers such as Sevrika [7] and Suryadi and Hendra [8] have recently conducted a study under a imilar topic.…”
Section: Discussionmentioning
confidence: 99%
“…The students can be invited to provide any pieces of information about what they need to learn in English through a study. In fact, need analysis has been seen as an important part of ELT at SMK since researchers such as Sevrika [7] and Suryadi and Hendra [8] have recently conducted a study under a imilar topic.…”
Section: Discussionmentioning
confidence: 99%
“…In the material development process, need analysis is used to identify the target materials or languages used in the teaching-learning process and to design an effective curriculum. The concept of need analysis is the first procedure to create and develop English for Specific Purpose (ESP) content (Sevrika, 2018;Zohoorian, 2015). Moreover, need analysis is aimed at helping the teachers or lecturers select the materials for teaching English based on the learner's needs (Andas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, several researchers previously reported that there was still an inappropriate English syllabus. Learning strategies designed in the syllabus need to consider the principles of learning and learning theory [7], henceforth, Sevrika did study to analyze students' needs on English learning material and found that students have a high level of difficulty in English learning materials [8]. She revealed that students need English materials that are easy to be understood.…”
Section: Introductionmentioning
confidence: 99%